Iowa Birdline update, March 27, 1993 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1993)
Summary of Iowa Birdline updates for March 27, 1993. The highlights for the update include sightings of the continued presence of a Black-throated Sparrow in Waterloo, a Cinnamon Teal with six Blue-winged Teal at Cone Marsh, and a Red-shouldered Hawk near Burlington. Epson - sheet feed/flatbed